A magnesium alloy-carbon fiber composite material with a magnesium scale-PA66 fiber net interlocking structure and a preparation method thereof

CN122976136APending Publication Date: 2026-10-27SOUTHWEAT UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611258762.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]本发明主要针对重要装备领域结构轻量化设计对于镁合金-碳纤维复合材料一体化、高性能化开发需求,胶接接头存在的界面易发生脱胶失效等突出问题,提供了一种通过激光雕刻联合平板静电纺丝原位构筑的镁鳞-PA66纤维网互锁结构的镁合金-碳纤维复合材料及其制备方法

Benefits of technology

本发明采用激光雕刻结合平板静电纺丝技术,成功构筑镁鳞-PA66纤维网互锁结构。采用激光雕刻处理镁合金表面,在镁合金表面制备排列规律的鱼鳞状突起,为机械咬合结构的构筑和纳米纤维网的黏附创造了有效的表面条件。采用静电纺丝处理激光雕刻后的镁合金表面,PA66纤维网与镁鳞结构形成半粘连结构,界面结合增强。形成的镁鳞-PA66纤维网互锁结构不仅实现了纳米纤维在镁鳞结构间的有效且均匀的黏附,减少了由于直接引入增强纤维所导致的纤维分布不均等问题,更通过鱼鳞状突起与PA66纤维网的深度嵌合互锁,联合构筑刚性机械咬合与准Z向柔性纤维桥连的双重增强体系。在复合材料受到外力作用时,能有效阻止或偏转材料内部的微裂纹扩展,提升了复合材料的力学性能,单搭接剪切强度可达19.32 MPa,有效解决了胶接界面脱胶失效的问题。此外,本发明的制备方法工艺简便、易于工业化生产,所制得的复合材料兼具轻量化与高抗剥离性能,有助于拓展镁合金-碳纤维复合材料在交通运输、汽车制造、电子设备及医疗器械等关键领域的轻量化应用市场。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122976136A_ABST
    Figure CN122976136A_ABST
Patent Text Reader

Abstract

The application provides a magnesium alloy-carbon fiber composite material with a magnesium scale-PA66 fiber net interlocking structure and a preparation method thereof, and belongs to the technical field of new materials. The magnesium alloy-carbon fiber composite material is formed by constructing a magnesium scale-PA66 fiber net interlocking structure between a magnesium alloy and a carbon fiber plate. The preparation method comprises the following steps: laser engraving is performed on the surface of the magnesium alloy to form a fish scale-shaped dot matrix, then a PA66 fiber net is constructed between the fish scale-shaped dot matrix through electrospinning, the carbon fiber plate and the treated magnesium alloy are placed in a resin pre-coating solution for standing and soaking, the magnesium alloy-carbon fiber composite material is obtained after the standing and soaking, and the magnesium alloy-carbon fiber composite material is obtained after the standing and soaking. The anchoring effect of the fish scale-shaped protrusions provides a quasi-vertical accommodation space for the epoxy adhesive and the PA66 fiber, the interface bonding is improved and defects are reduced through the pre-coating process, the interlocking structure formed has mechanical occlusion and fiber bridging effects, and the interface performance and mechanical performance between the magnesium alloy and the carbon fiber plate can be significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of novel materials technology, and particularly relates to a magnesium alloy-carbon fiber composite material with a magnesium scale-PA66 fiber mesh interlocking structure and its preparation method. Background Technology

[0002] Magnesium alloys combined with carbon fiber sheets, due to their outstanding lightweight characteristics and excellent mechanical properties, have shown broad application prospects in modern industry. These materials demonstrate significant application value in aerospace, high-end automobile manufacturing, precision electronic equipment, and high-performance medical devices. Magnesium alloys possess advantages such as low density, high specific strength, excellent damping performance, and ease of forming and processing. When combined with carbon fiber, the specific strength and specific stiffness of the overall structure are further improved, while retaining good damping and fatigue resistance properties, enabling long-term stability in harsh environments. To achieve a better balance between lightweighting and comprehensive performance, magnesium alloy-carbon fiber composites have received increasing attention. However, due to significant differences in the thermal expansion coefficient, surface energy, wettability, and mechanical properties of the magnesium alloy matrix and the carbon fiber resin composite, existing adhesive composite structures still face core technological bottlenecks. On the one hand, magnesium alloy surfaces are prone to forming a loose oxide layer, and the surface polarity has poor compatibility with the resin, resulting in insufficient wetting of the adhesive interface and weak interfacial bonding. On the other hand, under the influence of alternating loads, temperature cycling, and humid and hot environments, heterogeneous interfaces are prone to stress mismatch, which can lead to the initiation and propagation of interfacial microcracks, ultimately causing delamination and delamination failure of the adhesive interface, which seriously affects the structural strength stability of composite materials and the safety of practical applications.

[0003] Therefore, researching a magnesium alloy-carbon fiber composite material that can improve the compatibility of the heterogeneous interface between magnesium alloy and carbon fiber sheet, strengthen the interfacial bonding strength, suppress delamination defects, and improve the overall mechanical properties and service stability of the composite structure is a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention

[0004] This invention primarily addresses the need for integrated and high-performance development of magnesium alloy-carbon fiber composite materials in the lightweight design of critical equipment, and the prominent problem of interfacial debonding failure in adhesive joints. It provides a magnesium alloy-carbon fiber composite material with an interlocking magnesium scale-PA66 fiber mesh structure constructed in situ through laser engraving combined with flat electrospinning, and its preparation method. This invention introduces PA66 fiber mesh into the magnesium scale structure using laser engraving combined with flat electrospinning, strengthening the interfacial interaction between the magnesium alloy and the epoxy adhesive, and constructing a dual-reinforcement structure of fish-scale-like protrusion mechanical interlocking and quasi-Z-direction fiber bridging. This results in a magnesium alloy-carbon fiber composite material reinforced by an in-situ interlocking magnesium scale-PA66 fiber mesh structure constructed through laser engraving and flat electrospinning.

[0005] To achieve the above objectives, the present invention provides the following technical solution: One of the technical solutions of the present invention: This invention provides a magnesium alloy-carbon fiber composite material with a magnesium scale-PA66 fiber mesh interlocking structure, wherein the magnesium alloy-carbon fiber composite material is formed by bonding a magnesium scale-PA66 fiber mesh interlocking structure between magnesium alloy and carbon fiber materials.

[0006] Furthermore, the magnesium scale-PA66 fiber web interlocking structure is an integrated composite structure formed by the interlocking and tight interlocking of the magnesium scale structure and the PA66 fiber web.

[0007] Furthermore, the carbon fiber material is a carbon fiber board formed by alternating 0° fiber layers and 90° fiber layers to form basic units, and after laying ten sets of basic units, they are laid symmetrically with the center face of the board.

[0008] The second technical solution of the present invention: This invention also provides a method for preparing the magnesium alloy-carbon fiber composite material with the aforementioned magnesium scale-PA66 fiber mesh interlocking structure, comprising the following steps: (1) Laser engraving is performed on the surface of magnesium alloy to form a fish-scale dot matrix; (2) PA66 fiber web is constructed between the fish scale lattice by flat electrospinning technology, and a magnesium scale-PA66 fiber web interlocking structure is generated on the surface of the magnesium alloy. (3) After grinding and cleaning, the carbon fiber material and the magnesium alloy that forms the magnesium scale-PA66 fiber mesh interlocking structure are placed in the resin pre-coating solution and left to soak. After soaking, the material is taken out and glued. After being left to stand and cured, the magnesium alloy-carbon fiber composite material is obtained.

[0009] Beneficial Effects: This invention effectively improves the bonding performance of adhesive joints by treating the substrate surface and introducing reinforcing fibers before bonding. Specifically, the combined action of laser engraving and electrospinning technology forms an interlocking structure of magnesium scale-PA66 fiber web, which plays a crucial role in fiber formation, interface anchoring, and overall reinforcement. During electrospinning, the solution viscosity directly determines fiber formation and spinning stability; the PA66 solution itself possesses good viscosity and spinning characteristics, enabling the stable formation of uniform and continuous nanofibers. The prepared PA66 fiber web (a fishing net-like PA66 fiber coating) exhibits excellent toughness, mechanical strength, thermal stability, and interfacial compatibility, and can form a good bond with the epoxy adhesive layer.

[0010] Furthermore, the laser engraving speed in step (1) is 280-320 mm / s, the power is 22-26 W, and the frequency is 28-32 kHz.

[0011] Furthermore, the fish-scale lattice mentioned in step (1) is a fan-shaped fish-scale lattice; The width of the fan-shaped fish scale units in the fan-shaped fish scale lattice is 1.06-3.18 mm, and the distance between the edges of each unit is 0.53-1.59 mm.

[0012] Beneficial effects: Laser engraving technology constructs regular fan-shaped, fish-scale-like protrusions on the magnesium alloy surface, providing a stable anchoring structure and mechanical interlocking basis for the PA66 fiber mesh, significantly enhancing the integration of the fiber mesh with the magnesium alloy surface. The PA66 fiber trunk adheres to the protrusions, while the fiber ends move freely. Through resin flow, the fiber ends are driven to embed into the channels, forming a semi-adhesive structure. Quasi-Z-direction fiber bridging is constructed at the bonding interface, improving the interface's shear resistance, effectively preventing or deflecting the propagation of microcracks within the material, and further enhancing the bonding strength of the joint.

[0013] Furthermore, in step (1), after laser engraving is completed, the magnesium alloy needs to be placed in acetone for ultrasonic cleaning for 10 minutes, and then left to stand in a room temperature ventilated environment until the acetone completely evaporates.

[0014] Further, the specific process of step (2) is as follows: after mixing formic acid and acetic acid, add PA66, dissolve to obtain an electrospinning solution, and use the electrospinning solution to construct a PA66 fiber web between the fish scale lattice on the surface of the magnesium alloy using the flat electrospinning technology.

[0015] Furthermore, the areal density of the PA66 fiber mesh on the magnesium alloy surface is 0.045-0.105 g / m². 2 ; The electrospinning technology described herein uses a spinning voltage of 15-17 kV, a liquid supply rate of 0.7-0.9 mL / h, a distance of 15 cm between the spinning receiving plate and the magnesium alloy receiving plate, and a spinning receiving area of ​​283.53 cm². 2 .

[0016] Furthermore, the volume ratio of formic acid to acetic acid is 1:1, and the amount of PA66 added is 12% of the total mass of the formic acid and acetic acid mixed solution.

[0017] Further, the resin pre-coating solution in step (3) includes acetone and epoxy resin in a mass ratio of 9:1; The soaking time is 8-12 seconds.

[0018] Furthermore, before bonding in step (3), the mixture should be left to stand in a ventilated environment at room temperature until the acetone has completely evaporated.

[0019] Further, the adhesive used in step (3) is epoxy resin and curing agent in a volume ratio of 5:4; The settling time is 10-14 h, and after the resin is semi-cured, it is cured at a temperature of 50-70℃ for 72-120 h.

[0020] Beneficial Effects: This invention utilizes flat electrospinning technology to uniformly construct a PA66 fiber web between magnesium scales. The PA66 fibers tightly wrap around and embed between the fish-scale-like protrusions, forming a semi-adhesive structure. Through the anchoring effect of the magnesium scales, a quasi-vertical space is provided for the epoxy adhesive and PA66 fibers, enhancing the bonding performance of the joint. Furthermore, the resin pre-coating process improves interfacial bonding and reduces defects. When the adhesive layer is subjected to external force, the effective mechanical interlocking structure formed between the magnesium scales and the epoxy adhesive, together with the PA66 fiber web, absorbs and disperses the external force. The resulting quasi-Z-oriented bridging structure effectively prevents the propagation of microcracks, further enhancing the mechanical properties of the magnesium alloy-carbon fiber adhesive joint.

[0021] The beneficial effects of this invention compared to the prior art are as follows: This invention utilizes laser engraving combined with flat electrospinning technology to successfully construct a magnesium scale-PA66 fiber mesh interlocking structure. Laser engraving is applied to the magnesium alloy surface, creating regularly arranged fish-scale-like protrusions that provide effective surface conditions for the construction of the mechanical interlocking structure and the adhesion of the nanofiber mesh. Electrospinning is then applied to the laser-engraved magnesium alloy surface, forming a semi-adhesive structure between the PA66 fiber mesh and the magnesium scale structure, enhancing the interfacial bonding. The resulting magnesium scale-PA66 fiber mesh interlocking structure not only achieves effective and uniform adhesion of nanofibers within the magnesium scale structure, reducing problems such as uneven fiber distribution caused by directly introducing reinforcing fibers, but also, through the deep interlocking of the fish-scale protrusions and the PA66 fiber mesh, jointly constructs a dual reinforcement system of rigid mechanical interlocking and quasi-Z-axis flexible fiber bridging. When the composite material is subjected to external forces, it can effectively prevent or deflect the propagation of microcracks within the material, improving the mechanical properties of the composite material. The single-lap shear strength can reach 19.32 MPa, effectively solving the problem of adhesive interface debonding failure. Furthermore, the preparation method of the present invention is simple and easy to industrialize, and the resulting composite material has both lightweight and high peel resistance, which helps to expand the market for lightweight applications of magnesium alloy-carbon fiber composite materials in key fields such as transportation, automobile manufacturing, electronic equipment and medical devices. Attached Figure Description

[0022] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0023] Figure 1 This is a flowchart illustrating the preparation process of the magnesium alloy-carbon fiber composite material with a magnesium scale-PA66 fiber mesh interlocking structure in this invention. W For the width of the sample, T 1 represents the thickness of the magnesium alloy and carbon fiber composite material. T 2 represents the thickness of the adhesive layer. L 1 represents the overlap length. L 2 represents the length of the magnesium alloy and carbon fiber composite material; values ​​for each dimension are as follows: W =25.4 mm, T 1 = 3 mm, T 2 = 0.76 mm, L 1 = 25.4 mm, L 2 = 101.6 mm; Figure 2 This is a diagram illustrating the reinforcement mechanism of the magnesium alloy-carbon fiber composite material with a magnesium scale-PA66 fiber mesh interlocking structure in this invention. Figure 3 This is a model diagram showing the distribution of PA66 fiber web on the surface of the fan-shaped fish-scale protrusion structure in Embodiment 1 of the present invention; Figure 4 The images show the microstructure of the magnesium scale structure in the magnesium alloy-carbon fiber composite material prepared in Example 1 of this invention (a) and the microstructure of the magnesium scale-PA66 fiber web (b). Figure 5 The three-dimensional contour diagrams (a) and (b) of the magnesium scale-PA66 fiber web in the magnesium alloy-carbon fiber composite material prepared in Example 1 of the present invention are shown. Figure 6 The surface tension diagrams (a) and (b) of the magnesium alloy without treatment in Example 1 of the present invention are shown. Figure 7 This is an X-ray diffraction analysis diagram of PA66 fiber in Example 1 of the present invention; Figure 8 The bar chart shows the single-lap shear strength of the magnesium alloy-carbon fiber composite materials prepared in Examples 1-5 and Comparative Examples 1-4 of this invention. Detailed Implementation

[0024] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0025] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0026] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0027] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0028] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0029] In all embodiments of the present invention, the room temperature is 23±2℃.

[0030] The preparation process of the magnesium alloy-carbon fiber composite material with magnesium scale-PA66 fiber mesh interlocking structure in this invention is as follows: Figure 1 As shown; The reinforcement mechanism of magnesium alloy-carbon fiber composites with magnesium scale-PA66 fiber mesh interlocking structure is as follows: Figure 2 As shown.

[0031] Example 1 A method for preparing a magnesium alloy-carbon fiber composite material with a magnesium scale-PA66 fiber mesh interlocking structure includes the following steps: (1) Use a JLF30 laser engraving machine to engrave fan-shaped fish scale protrusions on the surface of magnesium alloy. Each fan-shaped fish scale protrusion is a unit. The width of each fan-shaped fish scale unit is 2.12 mm and the distance between the edges of each unit is 1.06 mm. The laser processing parameters are set to speed 300 mm / s, power 24 W, and frequency 30 kHz. After engraving, the magnesium alloy is placed in acetone for ultrasonic cleaning for 10 min. After taking it out, it is left to stand in a ventilated environment at room temperature until the acetone completely evaporates.

[0032] (2) After mixing 7 mL of formic acid and 7 mL of acetic acid evenly, PA66 particles were added (the amount of PA66 particles added was 12% of the total mass of the formic acid and acetic acid mixture). The mixture was continuously magnetically stirred at room temperature for 4 h. After complete dissolution, it was allowed to stand for 12 h to remove excess air bubbles, thus obtaining an electrospinning solution. PA66 fiber webs were then constructed on the magnesium alloy surface using flat electrospinning technology between the fish-scale lattice. The areal density of the PA66 fiber webs on the magnesium alloy surface was 0.045 g / m². 2 A magnesium scale-PA66 fiber web interlocking structure was formed on the surface of the magnesium alloy. The spinning voltage of the flat electrospinning technology was 16 kV, the liquid supply rate was 0.8 mL / h, the distance between the spinning receiving plate and the magnesium alloy receiving plate was 15 cm, and the spinning receiving area was 283.53 cm². 2 A model of PA66 fiber web distribution on the surface of a fan-shaped, fish-scale-like protrusion structure is shown below. Figure 3 As shown, through Figure 3 It can be seen that a PA66 fiber network is uniformly constructed between the laser-engraved fan-shaped fish scale-like protrusions. This fiber network is similar to a fishing net, forming a fishing net-like PA66 fiber coating. The PA66 fibers tightly wrap around and embed between the fish scale-like protrusions to form a semi-adhesive structure.

[0033] (3) Use 200# sandpaper to sand the surface of the carbon fiber board (the basic unit is formed by alternating 0° fiber layer and 90° fiber layer. After laying ten sets of basic units, they are laid symmetrically with the center face of the board). Place it in acetone for ultrasonic cleaning for 10 minutes. Then, place it and the magnesium alloy that has been treated by laser engraving and electrospinning in a resin pre-coating solution (a mixture of acetone and epoxy resin with a mass ratio of 9:1) and let it stand for 10 seconds. After soaking, take it out and let it stand in a ventilated environment at room temperature until the acetone completely evaporates, which takes about 1 minute.

[0034] (4) Place the treated magnesium alloy and carbon fiber plates on a mold (a single-lap adhesive positioning tooling mold used to constrain the overlap position and overlap size of the magnesium alloy plate and the carbon fiber plate), and use Araldite ®A two-component epoxy adhesive (AW106 epoxy resin and HV953U modified amine curing agent in a volume ratio of 5:4) was used for bonding, following ASTM D5868 standards. The adhesive was applied to a mold to achieve a bond thickness of 0.76 mm. After standing for 12 hours, a semi-cured preliminary product was obtained. The resulting experimental sample was transferred to a 60℃ drying oven and cured for 72 hours to achieve complete curing, yielding a magnesium alloy-carbon fiber composite material. The microstructure of the magnesium scale structure and the magnesium scale-PA66 fiber network in this composite material are shown below. Figure 4 As shown, the three-dimensional contour diagram is as follows Figure 5 As shown.

[0035] The surface tension of the untreated magnesium alloy substrate and the surface tension of the magnesium aluminate-PA66 fiber web were tested, and the results are as follows: Figure 6 As shown, through Figure 6 It can be seen that the contact angle of the untreated magnesium alloy substrate is 60.76 ± 1.83°, which has a certain degree of hydrophilicity; the contact angle of the magnesium scale-PA66 fiber mesh surface is close to 0°, and water droplets spread completely on the surface, achieving a superhydrophilic effect. It can be seen that the surface wettability of the material is significantly improved after composite modification.

[0036] X-ray diffraction analysis of PA66 fibers yielded the following results: Figure 7 As shown, through Figure 7 It can be seen that the PA66 fiber exhibits characteristic diffraction peaks of the α crystal form, which are attributed to the α (100) and α (010 / 110) crystal planes, respectively, indicating that the obtained PA66 fiber is mainly a thermodynamically stable α crystal structure.

[0037] Gaskets were bonded to the back of the non-lapped end of the magnesium alloy and the back of the non-lapped end of the carbon fiber sheet in the prepared magnesium alloy-carbon fiber composite material. The single lap shear strength of the magnesium alloy-carbon fiber composite material prepared in Example 1 was tested according to GB / T 44302-2024. The results showed that ( Figure 8 The single lap shear strength of the magnesium alloy-carbon fiber composite material prepared in Example 1 reached 18.57 MPa.

[0038] Example 2 A method for preparing a magnesium alloy-carbon fiber composite material with an interlocking structure of magnesium scale-PA66 fiber mesh differs from Example 1 in that: in step (2), the areal density of the PA66 fiber mesh on the magnesium alloy surface is 0.060 g / m². 2 ; The remaining preparation methods are the same as in Example 1.

[0039] Gaskets were bonded to the back of the non-lapped end of the magnesium alloy and the back of the non-lapped end of the carbon fiber sheet of the prepared magnesium alloy-carbon fiber composite material. The single lap shear strength of the magnesium alloy-carbon fiber composite material prepared in Example 2 was tested according to GB / T 44302-2024. The results showed that the single lap shear strength of the magnesium alloy-carbon fiber composite material prepared in Example 2 reached 18.87 MPa.

[0040] Example 3 A method for preparing a magnesium alloy-carbon fiber composite material with an interlocking structure of magnesium scale-PA66 fiber mesh differs from Example 1 in that: in step (2), the areal density of the PA66 fiber mesh on the magnesium alloy surface is 0.075 g / m². 2 ; The remaining preparation methods are the same as in Example 1.

[0041] Gaskets were bonded to the back of the non-lapped end of the magnesium alloy and the back of the non-lapped end of the prepared magnesium alloy-carbon fiber composite material. The single-lap shear strength of the magnesium alloy-carbon fiber composite material prepared in Example 3 was tested according to GB / T 44302-2024. The results showed that ( Figure 8 The single lap shear strength of the magnesium alloy-carbon fiber composite material prepared in Example 3 reached 19.32 MPa.

[0042] Example 4 A method for preparing a magnesium alloy-carbon fiber composite material with an interlocking structure of magnesium scale-PA66 fiber mesh differs from Example 1 in that: in step (2), the areal density of the PA66 fiber mesh on the magnesium alloy surface is 0.090 g / m². 2 ; The remaining preparation methods are the same as in Example 1.

[0043] Gaskets were bonded to the back of the non-lapped end of the magnesium alloy and the back of the non-lapped end of the prepared magnesium alloy-carbon fiber composite material. The single-lap shear strength of the magnesium alloy-carbon fiber composite material prepared in Example 4 was tested according to GB / T 44302-2024. The results showed that ( Figure 8 The single lap shear strength of the magnesium alloy-carbon fiber composite material prepared in Example 4 reached 18.24 MPa.

[0044] Example 5 A method for preparing a magnesium alloy-carbon fiber composite material with an interlocking structure of magnesium scale-PA66 fiber mesh differs from Example 1 in that: in step (2), the areal density of the PA66 fiber mesh on the magnesium alloy surface is 0.105 g / m². 2 ; The remaining preparation methods are the same as in Example 1.

[0045] Gaskets were bonded to the back of the non-lapped end of the magnesium alloy and the back of the non-lapped end of the prepared magnesium alloy-carbon fiber composite material. The single-lap shear strength of the magnesium alloy-carbon fiber composite material prepared in Example 5 was tested according to GB / T 44302-2024. The results showed that ( Figure 8 The single lap shear strength of the magnesium alloy-carbon fiber composite material prepared in Example 5 reached 18.11 MPa.

[0046] Comparative Example 1 A method for preparing a magnesium alloy-carbon fiber composite material, which does not involve laser engraving or flat electrospinning, and does not require immersion in a resin pre-coating solution. The specifications of the magnesium alloy and carbon fiber plates used in the experiment are the same as in Example 1. The specific preparation process is as follows: Magnesium alloy and carbon fiber plates were ultrasonically cleaned in acetone for 10 min. AW106 / HV953U two-component epoxy adhesive was prepared at a volume ratio of 5:4. This two-component epoxy adhesive was applied to the bonding area of ​​the magnesium alloy and carbon fiber plates. According to the ASTM D5868 standard bonding model, the adhesive was bonded on the mold to achieve a bonding layer thickness of 0.76 mm. After standing for 12 h, a semi-cured preliminary product was obtained. The obtained experimental sample was transferred to a 60℃ drying oven and cured for 72 h to achieve complete curing, thus obtaining the magnesium alloy-carbon fiber composite material.

[0047] Gaskets were bonded to the back of the non-lapped end of the magnesium alloy and the back of the non-lapped end of the carbon fiber sheet of the prepared magnesium alloy-carbon fiber composite material. The single lap shear strength of the magnesium alloy-carbon fiber composite material prepared in Comparative Example 1 was tested according to GB / T 44302-2024. The results showed that the single lap shear strength of the magnesium alloy-carbon fiber composite material prepared in Comparative Example 1 was 10.35 MPa. Compared with the example, the mechanical properties of the composite material were significantly reduced.

[0048] Comparative Example 2 A method for preparing a magnesium alloy-carbon fiber composite material, without flat electrospinning, is disclosed. The specifications of the magnesium alloy and carbon fiber plates used in the experiment are the same as in Example 1. The specific preparation process is as follows: (1) Use a JLF30 laser engraving machine to engrave fan-shaped fish scale protrusions on the surface of magnesium alloy. Each fan-shaped fish scale protrusion is a unit. The width of each fan-shaped fish scale unit is 2.12 mm and the distance between the edges of each unit is 1.06 mm. The laser processing parameters are set to speed 300 mm / s, power 24 W, and frequency 30 kHz. After engraving, the magnesium alloy is placed in acetone for ultrasonic cleaning for 10 min. After taking it out, it is left to stand in a ventilated environment at room temperature until the acetone completely evaporates.

[0049] (2) Use 200# sandpaper to sand the surface of the carbon fiber plate and ultrasonically clean it in acetone for 10 min. Then, place it and the laser-engraved magnesium alloy in a resin pre-coating solution (a mixture of acetone and epoxy resin with a mass ratio of 9:1) and let it stand for 10 s. After soaking, take it out and let it stand in a ventilated environment at room temperature until the acetone completely evaporates, which takes about 1 min.

[0050] (3) Place the treated magnesium alloy and carbon fiber plate on the mold and use Araldite ® A two-component epoxy adhesive, AW106 / HV953U (with a volume ratio of 5:4 for AW106 epoxy resin and HV953U modified amine curing agent), was used for bonding. The bonding process followed ASTM D5868 standards. The adhesive was applied to a mold to achieve a bond thickness of 0.76 mm. After standing for 12 hours, a semi-cured preliminary product was obtained. The resulting experimental sample was then transferred to a 60°C drying oven and cured for 72 hours to achieve complete curing, yielding a magnesium alloy-carbon fiber composite material.

[0051] Gaskets were bonded to the back of the non-lapped end of the magnesium alloy and the back of the non-lapped end of the carbon fiber sheet of the prepared magnesium alloy-carbon fiber composite material. The single lap shear strength of the magnesium alloy-carbon fiber composite material prepared in Comparative Example 2 was tested according to GB / T 44302-2024. The results showed that the single lap shear strength of the magnesium alloy-carbon fiber composite material prepared in Comparative Example 2 was 17.76 MPa. Compared with the example, the mechanical properties of the composite material were reduced.

[0052] Comparative Example 3 A method for preparing a magnesium alloy-carbon fiber composite material, without laser engraving, is disclosed. The specifications of the magnesium alloy and carbon fiber plates used in the experiment are the same as in Example 1. The specific preparation process is as follows: (1) After mixing 7 mL of formic acid and 7 mL of acetic acid evenly, PA66 particles were added (the amount of PA66 particles added was 12% of the total mass of the formic acid and acetic acid mixture). The mixture was continuously magnetically stirred at room temperature for 4 h. After complete dissolution, it was allowed to stand for 12 h to remove excess air bubbles, thus obtaining an electrospinning solution. PA66 fiber webs were then constructed on the surface of a magnesium alloy using a flat electrospinning technique. The areal density of the PA66 fiber webs on the magnesium alloy surface was 0.075 g / m². 2 The spinning voltage of the flat electrospinning technology was 16 kV, the liquid supply rate was 0.8 mL / h, the distance between the spinning receiving plate and the magnesium alloy receiving plate was 15 cm, and the spinning receiving area was 283.53 cm². 2 .

[0053] (2) Use 200# sandpaper to sand the surface of the carbon fiber plate and ultrasonically clean it in acetone for 10 minutes. Then, place it and the magnesium alloy after electrospinning in a resin pre-coating solution (a mixture of acetone and epoxy resin with a mass ratio of 9:1) and let it stand for 10 seconds. After soaking, take it out and let it stand in a ventilated environment at room temperature until the acetone completely evaporates, which takes about 1 minute.

[0054] (3) Place the treated magnesium alloy and carbon fiber plate on the mold and use Araldite ® A two-component epoxy adhesive, AW106 / HV953U (with a volume ratio of 5:4 for AW106 epoxy resin and HV953U modified amine curing agent), was used for bonding. The bonding process followed ASTM D5868 standards. The adhesive was applied to a mold to achieve a bond thickness of 0.76 mm. After standing for 12 hours, a semi-cured preliminary product was obtained. The resulting experimental sample was then transferred to a 60°C drying oven and cured for 72 hours to achieve complete curing, yielding a magnesium alloy-carbon fiber composite material.

[0055] Gaskets were bonded to the back of the non-lapped end of the magnesium alloy and the back of the non-lapped end of the prepared magnesium alloy-carbon fiber composite material. The single-lap shear strength of the magnesium alloy-carbon fiber composite material prepared in Comparative Example 3 was tested according to GB / T 44302-2024. The results showed that ( Figure 8 The single lap shear strength of the magnesium alloy-carbon fiber composite material prepared in Comparative Example 3 was 12.10 MPa. Compared with the example, the mechanical properties of the composite material were significantly reduced.

[0056] Comparative Example 4 A method for preparing a magnesium alloy-carbon fiber composite material differs from Example 2 in that: in step (1), the fan-shaped fish scale-like protrusions are not carved, but a solid circular array with a diameter of 2.12 mm and an edge spacing of 1.06 mm for each unit is carved; The remaining preparation methods are the same as in Example 2.

[0057] Gaskets were bonded to the back of the non-lapped end of the magnesium alloy and the back of the non-lapped end of the prepared magnesium alloy-carbon fiber composite material. The single-lap shear strength of the magnesium alloy-carbon fiber composite material prepared in Comparative Example 4 was tested according to GB / T 44302-2024. The results showed that ( Figure 8 The single lap shear strength of the magnesium alloy-carbon fiber composite material prepared in Comparative Example 4 was 14.30 MPa. Compared with the example, the mechanical properties of the composite material were significantly reduced.

[0058] Comparative Example 5 A method for preparing a magnesium alloy-carbon fiber composite material, without flat electrospinning and resin pre-coating, uses magnesium alloy and carbon fiber plates with the same specifications as in Example 1. The specific preparation process is as follows: (1) Use a JLF30 laser engraving machine to engrave fan-shaped fish scale protrusions on the surface of magnesium alloy. Each fan-shaped fish scale protrusion is a unit. The width of each fan-shaped fish scale unit is 2.12 mm and the distance between the edges of each unit is 1.06 mm. The laser processing parameters are set to speed 300 mm / s, power 24 W, and frequency 30 kHz. After engraving, the magnesium alloy is placed in acetone for ultrasonic cleaning for 10 min. After taking it out, it is left to stand in a ventilated environment at room temperature until the acetone completely evaporates.

[0059] (2) Use 200# sandpaper to sand the surface of the carbon fiber board and place it in acetone for ultrasonic cleaning for 10 min. Let it stand in a room temperature and ventilated environment until the acetone completely evaporates, which takes about 1 min.

[0060] (3) Place the treated magnesium alloy and carbon fiber plate on the mold and use Araldite ® A two-component epoxy adhesive, AW106 / HV953U (with a volume ratio of 5:4 for AW106 epoxy resin and HV953U modified amine curing agent), was used for bonding. The bonding process followed ASTM D5868 standards. The adhesive was applied to a mold to achieve a bond thickness of 0.76 mm. After standing for 12 hours, a semi-cured preliminary product was obtained. The resulting experimental sample was then transferred to a 60°C drying oven and cured for 72 hours to achieve complete curing, yielding a magnesium alloy-carbon fiber composite material.

[0061] Gaskets were bonded to the back of the non-lapped end of the magnesium alloy and the back of the non-lapped end of the prepared magnesium alloy-carbon fiber composite material. The single-lap shear strength of the magnesium alloy-carbon fiber composite material prepared in Comparative Example 5 was tested according to GB / T 44302-2024. The results showed that ( Figure 8 The single lap shear strength of the magnesium alloy-carbon fiber composite material prepared in Comparative Example 5 was 15.54 MPa. Compared with the example, the mechanical properties of the composite material were significantly reduced.

[0062] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A magnesium alloy-carbon fiber composite material with a magnesium scale-PA66 fiber mesh interlocking structure, characterized in that, The magnesium alloy-carbon fiber composite material is formed by bonding a magnesium scale-PA66 fiber mesh interlocking structure between the magnesium alloy and carbon fiber materials.

2. A method for preparing a magnesium alloy-carbon fiber composite material with a magnesium scale-PA66 fiber mesh interlocking structure as described in claim 1, characterized in that, Includes the following steps: (1) Laser engraving is performed on the surface of magnesium alloy to form a fish-scale dot matrix; (2) PA66 fiber web is constructed between the fish scale lattice by flat electrospinning technology, and a magnesium scale-PA66 fiber web interlocking structure is generated on the surface of the magnesium alloy. (3) After grinding and cleaning, the carbon fiber material and the magnesium alloy that forms the magnesium scale-PA66 fiber mesh interlocking structure are placed in the resin pre-coating solution and left to soak. After soaking, the material is taken out and glued. After being left to stand and cured, the magnesium alloy-carbon fiber composite material is obtained.

3. The preparation method according to claim 2, characterized in that, The laser engraving speed in step (1) is 280-320 mm / s, the power is 22-26 W, and the frequency is 28-32 kHz.

4. The preparation method according to claim 2, characterized in that, The fish-scale lattice mentioned in step (1) is a fan-shaped fish-scale lattice; The width of the fan-shaped fish scale units in the fan-shaped fish scale lattice is 1.06-3.18 mm, and the distance between the edges of each unit is 0.53-1.59 mm.

5. The preparation method according to claim 2, characterized in that, The specific process of step (2) is as follows: after mixing formic acid and acetic acid, add PA66 and dissolve to obtain an electrospinning solution. The electrospinning solution is used to construct a PA66 fiber web between the fish scale lattice on the surface of the magnesium alloy using flat electrospinning technology.

6. The preparation method according to claim 5, characterized in that, The areal density of the PA66 fiber mesh on the magnesium alloy surface is 0.045-0.105 g / m². 2 ; The electrospinning technology described above uses a spinning voltage of 15-17 kV, a liquid supply rate of 0.7-0.9 mL / h, a distance of 15 cm between the spinning receiving plate and the magnesium alloy receiving plate, and a spinning receiving area of ​​283.53 cm². 2 .

7. The preparation method according to claim 2, characterized in that, The resin pre-coating solution mentioned in step (3) includes acetone and epoxy resin in a mass ratio of 9:1; The soaking time is 8-12 seconds.

8. The preparation method according to claim 2, characterized in that, The adhesive used in step (3) is epoxy resin and curing agent in a volume ratio of 5:4; The settling time is 10-14 h, and after the resin is semi-cured, it is cured at a temperature of 50-70℃ for 72-120 h.